Harmonization of Regulations on the Digitalization of Government Financial Accountability and Bureaucratic Reform at the Ministry of Communications and Digital Affairs - Evi Fitriani; Irsyaf Marsal; Irwan Triadi (International Journal of Social Sciences and Humanities, 2026)
This study examines regulatory harmonisation in the digitalisation of state financial accountability and bureaucratic reform at the Ministry of Communication and Digital Affairs (Komdigi) of the Republic of Indonesia. Digital financial governance through DiGi.Ka, MonSAKTI, and OMSPAN, alongside Komdigi’s role as the national Chief Technology Officer for the Electronic-Based Government System (SPBE), remains constrained by regulatory fragmentation, overlapping authority, and legal uncertainty concerning state losses in intangible digital assets. This study analyses the configuration of authority and regulatory gaps in Komdigi’s financial system, and formulates an appropriate regulatory reform model to support integrated government financial governance. Using normative legal research with statute, analytical, and conceptual approaches, this study relies on secondary legal materials collected through library research and analysed qualitatively. The findings show that Komdigi’s financial authority remains sectoral and fragmented, vertically governed by state finance and treasury laws while horizontally intersecting with electronic information and digital transformation regulations. This creates a legal vacuum in accountability standards for dynamic digital transactions and overlapping supervision. The study recommends a collaborative-governance-based harmonisation model through procedural codification, authority redefinition, and system integration to achieve accountable, legally certain, and effective bureaucratic reform.